Molecular-Biological Methods of Quality Control of Biological Active Substances Produced by Recombinant DNA Technology - E. D. Mytsa; N. V. Chertova; E. V. Elbert; A. S. Sukhno; R. A. Volkova; V. A. Merkulov (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Biotechnological products manufactured by recombinant DNA technology are widely used nowadays. According to the national and  international requirements the amount of residual host cell DNA in  such products should not exceed 10 ng per dose. However, for  products intended for frequent or long-term use, this amount must  not exceed 100 pg per dose. This article describes methods most  frequently used for quantification of residual host cell DNA in  biological active substances contained in biotechnological products:  molecular hybridization with biotin- or digoxigenin-labelled DNA- probes (semiquantitative method), Threshold system, real-time PCR, method based on the use of a fluorescent reagent (assays). If  a method based on the use of a fluorescent reagent or real-time PCR are used to replace the current procedure, it is necessary to  demonstrate their validity, e.g. by comparing the results of residual DNA quantification obtained by the two methods — the new one and the current one. The article dwells upon the advantages and  disadvantages of the methods and potential sources of uncertainty.  It highlights the importance of using appropriately certified reference standards and retention samples. The biological active substances  included into the State Register of Medicinal Products conform to the international requirements in terms of the amount of residual host cell DNA.